Improving Patients’ Sleep in an Acute Mental Health Ward Using Non-Pharmacological Interventions - Theodoros Mavrogiannidis; Ghada Alshehabi; Alessandro Malfatto (BJPsych Open)
Aims: Interruption of sleep-wake behavioural patterns and circadian rhythms has been associated with the development and worsening of a range of mental health disorders, including depression, bipolar disorder, and schizophrenia, and specific high-risk outcomes such as aggression and suicidality. In full knowledge of the above, we aimed to improve patients’ self-reported sleep quality in an acute male ward, by 20% by the end of January 2025.